Testimony, credit, and blame - RYAN, Shane (Institutional Knowledge at Singapore Management University, 2020)
This paper examines ordinary people’s responses to Jennifer Lackey’s Chicago Visitor case. In particular it examines responses regarding the case from participants with Taiwanese backgrounds and US backgrounds. The Chicago Visitor case is one of the most influential cases in epistemology in recent years and plays a significant role in a number of debates in epistemology. First, the case is used to suggest that the Credit View is mistaken. Second, the case seems to pose a problem for a virtue epistemological account of the nature of knowledge. Our paper explores these points in relation to our survey results, which show that participants believe that the protagonist in the case does have knowledge and that the protagonist deserves some credit for his true belief. Our aim in this paper, however, isn’t only to discover evidence bearing on the discussion of the Chicago Visitor case and cross cultural differences related to that case, we are also interested in what else the case might tell us about epistemic agency. For this reason we also asked participants to tell us to what extent they thought that the protagonist would be at fault in a case in which their belief turned out to be false. Here most of the participants found that the protagonist would indeed bear some fault in such circumstances. Our survey results also show, however, that participants of US background tend to be likely to attribute less fault to the testimonial recipient in bad testimonial cases, than their Taiwanese counterparts. More generally, we explore what the result regarding fault can tell us about epistemic agency.